A study on factor contributing to customer satisfaction towards Anika Insurance Broker / Tengku Muhammad Hazwan Tengku Hashim Badli - Tengku Hashim Badli, Tengku Muhammad Hazwan (2011)
The research is focusing on the “Factor Contributing to Customer Satisfaction towards Anika Insurance Broker”. Even though the Anika Insurance Broker already establish since 1969, they still not get 100% customer satisfaction. The research is done to identify the factor contribute to customer satisfaction towards Anika Insurance Broker Sdn Bhd. The independent variable for this research is knowledge of the product, competitive edge, fulfilling customer need and experience in term of insurance. The research was conducted in Kuala Lumpur area and 30 questionnaires were distributed to clients that use Anika Insurance Broker service around the Kuala Lumpur area. The researcher use primary and secondary data in order to obtain the data. Data analyzed using the reliability test, descriptive statistics and backward elimination. Based on the analysis, the result showed that knowledge of the product is the most contributing factor when it comes to customer satisfaction towards Anika Insurance Broker Sdn Bhd.